Application of the Concept of Low-Cost Airline in Air Transport - Khachatryan, Gegham (Bulletin of Yerevan University G: Economics, 2021)
The subject of research is the costs of airlines. The purpose of the study is to confirm or deny the possibility of creating low-cost airlines as part of the Armenian air fleet. The research task is to find ways to reduce costs by calculating the costs of a traditional airline. The novelty of the study reveals the cost of reduced-cost items in the transportation tariff. The conclusion is made about the possibility of halving the cost of passenger transportation. The efficiency indicators of the low-cost airline have been calculated. The practical significance of the research results lies in increasing the validity of the creation of low-cost airlines in the country that is engaged in air transportation, confirming in practice the possibility of performing passenger transportation at lower prices than existing traditional airlines. The practical value of the results obtained lies in the possibility of using them for the implementation of measures to reduce tariffs in order to increase the competitiveness of airlines. The research methodology includes analytical, computational, and statistical methods. The scientific results show how much it is possible to reduce the costs of traditional airlines and bring them closer to the level of costs of low-cost airlines.
Keywords: air company; traditional; low-cost; cost item; tariff; transportation